Ragazzi italiani negli Stati Uniti - Bruna Bianchi (Mélanges de la Casa de Velázquez)
The first Italian immigrants to worry and alarm public opinion in America were the street organ grinders (1856-1876). They left their hometowns following an «employer» and, once in America, led a life of hardship, suffering exploitation and ill-treatment. During the period of the Great Emigration (1876-1910), when over four million Italians disembarked in the United States, the organ boys disappeared from the streets and were replaced by newspaper boys, porters and shoe shiners. Street trades were the prerogative of the children of Italian immigrants for a very long time but they gradually wormed their way into the rapidly expanding world of factory work, the mines and building sites. From 1880 to 1920 the percentage of Italian teenagers introduced precociously into the working world was only lower than that of the Afro-Americans. Very often they were responsible for supporting their families and this situation continued throughout the years of the Great Depression. It was only in the mid -1930’s that the number of Italian children in schools began to rise, their financial condition improved and their introduction into the new society began.